Stimulation of type I collagen activity in healing of pulp perforation - Sri Kunarti (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2008)
Background: TGF-β1 is a connective tissue stimulant, potential regulator for tissue repair, and promoter in wound healing. The healing of pulp perforation is decided by quantity and quality of new collagen deposition. TGF-β1 upregulates collagen transcription. However, after several weeks production of type I collagen synthesis is stopped and enzymatic degradation of collagen matrix will occur. Purpose: Observe synthesis type I collagen during the process of pulp perforation healing in 7, 14, and 21 days after being treated using TGF-β1. Methods: This research in vivo from orthodontic patients indicated for premolar extraction, between ages 10–15 years. A class V cavity preparation was created in the buccal aspect 1 mm above gingival margin until pulp exposure. Cavity was irrigated slowly with saline solution and dried with a sterile small cotton pellet. The sterile absorbable collagen membrane used, soaked with 5 μl of TGF-β1. It was covered by teflon pledge to separate from glass ionomer cement as restoration. Evaluated on day 7th, 14th, and 21st. All samples were extracted and prepared for immunohystochemical examination. Result: Data were analyzed by t-test. There was significant difference in synthesis type I collagen compared between 7–14 days and 7–21 days after treatment by TGF-β1 also Ca(OH)2. There was significant difference compared between TGF-β1 and Ca(OH)2 in 14–21 days after treatment (means TGF-β1 > Ca(OH)2). Conclusion: Elevation of synthesis type 1 collagen by TGF-β1 in 20 mg/ml.